Material flow cost accounting for a traditional cottage industry: Batik / Noreena Nordin - Noreena, Nordin (2017)
The pursuit of achieving optimal productivity has always being the primary objectives of any business or manufacturers. There are numerous ways to achieve optimal productivity and one of the initiatives is by applying the concept of Material Flow Cost Analysis (MFCA) to manufacturing processes in assessing material losses, thus reducing manufacturing cost. Furthermore, application of MFCA to manufacturing processes creates positive impacts to the environment and in the long run, benefits the company involved by optimizing productivity without compromising the environmental condition. In Malaysia, batik industry is categorized as a cottage and handicraft industry because it involves the use of traditional methods and tools. The nature of business of batik makers are usually family oriented and as expected, the margin of profit is relatively small compared to commercial batik makers that utilizes high technology machineries and methods to provide customers with cheaper and consistent supply of batiks. Nevertheless, the traditionally produced batiks always has its customers due to its uniqueness and intricate design since the design created depended on the batik artisan creativity and this makes traditionally made batiks appealing to the local and international customers. This research shows the application of MFCA in the traditional batik making processes in a small batik making enterprise, ABC Batik Kraf which mainly still utilizes traditional means of methods and processes to make batik. By conducting MFCA analysis on the processes done in ABC Batik Kraf, material losses were identified in terms of monetary and physical unit. Identification of these losses enables reduction of material loss and reduced wastage for each process during the batik making. The study was carried out on the specific batik making technique, which is making batik with block print. The associated cost of products and material losses of each process are identified and combined into one cost centre for ease of calculation. The MFCA results shows that material cost accounted for 56.67% of the total production cost while other cost such as the energy cost comprises of 0.69% of the total production cost and 42.64% which is the system cost, covers the remaining total production cost. The cost allocated for material losses was 24.44% of the total production cost Prior to the MFCA analysis, the batik makers from ABC Batik Kraf believed in their capability to produce batik kraf with minimum of 95% product yield rate, however based on MFCA analysis, this number is not achievable and ABC Batik Kraf have to implement improvements in order to increase its productivity and reduce material loss. Improvements can be made via various steps, such as reducing material loss, optimizing energy usage and improvising steps involved during batik making.